Abnormal Rat Cortical Development Induced by Ventricular Injection of rHMGB1 Mimics the Pathophysiology of Human Cortical Dysplasia - Yang, Xiaolin; Zhang, Xiaoqing; Ma, Yuanshi; Wang, Zhongke; Huang, Kaixuan; Liu, Guolong; Shen, Kaifeng; Zhu, Gang; Wang, Tingting; Lv, Shengqing; Zhang, Chunqing; Yang, Hui; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cortical dysplasia (CD) is a common cause of drug-resistant epilepsy. Increasing studies have implicated innate immunity in CD with epilepsy. However, it is unclear whether innate immune factors induce epileptogenic CD. Here, we injected recombinant human High Mobility Group Box 1 (rHMGB1) into embryonic rat ventricles to determine whether rHMGB1 can induce epileptogenic CD with pathophysiological characteristics similar to those of human CD. Compared with controls and 0.1 μg rHMGB1-treated rats, the cortical organization was severely disrupted in the 0.2 μg rHMGB1-treated rats, and microgyria and heterotopia also emerged; additionally, disoriented and deformed neurons were observed in the cortical lesions and heterotopias. Subcortical heterotopia appeared in the white matter and the gray-white junction of the 0.2μg rHMGB1-treated rats. Moreover, there was decreased number of neurons in layer Ⅴ-Ⅵ and an increased number of astrocytes in layer Ⅰ and Ⅴ of the cortical lesions. And the HMGB1 antagonist dexmedetomidine alleviated the changes induced by rHMGB1. Further, we found that TLR4 and NF-κB were increased after rHMGB1 administration. In addition, the excitatory receptors, N-methyl-D-aspartate receptor 1(NR1), 2A (NR2A), and 2B (NR2B) immunoreactivity were increased, and immunoreactivity of excitatory amino acid transporter 1 (EAAT1) and 2 (EAAT2) were reduced in 0.2 μg rHMGB1-treated rats compared with controls. While there were no differences in the glutamic acid decarboxylase 65/67 (GAD65/67) immunoreactivity between the two groups. These results indicate that the excitation of cortical lesions was significantly increased. Furthermore, electroencephalogram (EEG) showed a shorter latency of seizure onset and a higher incidence of status epilepticus in the 0.2 μg rHMGB1-treated rats; the frequency and amplitude of EEG were higher in the treated rats than controls. Intriguingly, spontaneous electrographic seizure discharges were detected in the 0.2 μg rHMGB1-treated rats after 5 months of age, and spike-wave discharges of approximately 8 Hz were the most significantly increased synchronous propagated waves throughout the general brain cortex. Taken together, these findings indicate that rHMGB1 exposure during pregnancy could contribute to the development of epileptogenic CD, which mimicked some pathophysiological characteristics of human CD.